Assessment of severe malnutrition among hospitalized children in rural Kenya: comparison of weight for height and mid upper arm circumference. - Berkley, J; Mwangi, I; Griffiths, K; Ahmed, I; Mithwani, S; English, M; Newton, C; Maitland, K (2005)
CONTEXT: Severe malnutrition has a high mortality rate among hospitalized children in sub-Saharan Africa. However, reports suggest that malnutrition is often poorly assessed. The World Health Organization recommends using weight for height, but this method is problematic and often not undertaken in practice. Mid upper arm circumference (MUAC) and the clinical sign "visible severe wasting" are simple and inexpensive methods but have not been evaluated in this setting. OBJECTIVES: To evaluate MUAC and visible severe wasting as predictors of inpatient mortality at a district hospital in sub-Saharan Africa and to compare these with weight-for-height z score (WHZ). DESIGN, SETTING, AND PARTICIPANTS: Cohort study with data collected at admission and at discharge or death. Predictive values for inpatient death were determined using the area under receiver operating characteristic curves. Participants were children aged 12 to 59 months admitted to a district hospital in rural Kenya between April 1, 1999, and July 31, 2002. MAIN OUTCOME MEASURE: MUAC, WHZ, and visible severe wasting as predictors of inpatient death. RESULTS: Overall, 4.4% (359) of children included in the study died while in the hospital. Sixteen percent (1282/8190) of admitted children had severe wasting (WHZ < or =-3) (n = 756), kwashiorkor (n = 778), or both. The areas under the receiver operating characteristic curves for predicting inpatient death did not significantly differ (MUAC: 0.75 [95% confidence interval, 0.72-0.78]; WHZ: 0.74 [95% confidence interval, 0.71-0.77]) (P = .39). Although sensitivity and specificity for subsequent inpatient death were 46% and 91%, respectively, for MUAC less than or equal to 11.5 cm, 42% and 92% for WHZ less than or equal to -3, and 47% and 93% for visible severe wasting, the 3 indices identified different sets of children and were independently associated with mortality. Clinical features of malnutrition were significantly more common among children with MUAC less than or equal to 11.5 cm than among those with WHZ less than or equal to -3. CONCLUSIONS: MUAC is a practical screening tool that performs at least as well as WHZ in predicting subsequent inpatient mortality among severely malnourished children hospitalized in rural Kenya. Visible severe wasting is also a potentially useful sign at this level, providing appropriate training has been given.